Strengthening Educational Accountability in Elementary School: The Role of Principals’ Transformational Leadership and Data-Based Planning - Ima Puji Astuti; Widya Kusumaningsih; Nurkolis Nurkolis (AL-ISHLAH: Jurnal Pendidikan, 2025)
Educational accountability is crucial in ensuring transparency and performance in schools. This study investigates the influence of principals’ transformational leadership and data-based planning on educational accountability in elementary schools in Boja District, Kendal Regency, Central Java. A quantitative approach with a causal-comparative design was employed. The study involved 103 elementary school teachers selected through proportional random sampling. Data were collected using validated questionnaires and analyzed through statistical procedures, including normality, linearity, multicollinearity, and hypothesis testing. The results indicate that principals’ transformational leadership has a significant effect on educational accountability, with an F-value of 613.153 (F-table = 3.94), a significance level of 0.000 (0.05), and an R-square of 85.9%, indicating a very strong effect. Likewise, data-based planning significantly influences educational accountability, evidenced by an F-value of 685.312, a significance level of 0.000, and an R-square of 87.2%. Furthermore, the combined effect of transformational leadership and data-based planning yields an F-value of 429.952, with a significance level of 0.000 and an R-square of 89.5%, demonstrating a very strong joint influence. These findings underscore the importance of transformational leadership and data-driven planning as strategic factors in enhancing school accountability. Principals who exhibit visionary leadership and utilize data effectively contribute significantly to transparent and effective school governance. Transformational leadership and data-based planning are critical to strengthening educational accountability in elementary schools. Policies and training programs should support these competencies among school leaders.